0508 Transcranial Magnetic Stimulation Shows Favorable Response for Insomnia in Depression with Greater Response in Males and in Those Less Than 65 Years of Age. (27th May 2020) - Stultz, D J; Osburn, S; Burns, T; Stanley, N; Walton, R; Cope, A; Pawlowska-Wajswol, S
Abstract: Introduction: Transcranial Magnetic Stimulation (TMS) is FDA approved for the treatment of resistant depression and multiple studies have demonstrated improvement of insomnia in both those with and without depression. Methods: 50 patients were studied while undergoing TMS treatment for resistant depression and utilizing the Patient Health Questionnaire-9 (PHQ-9), the Beck Depression Inventory (BDI), the Insomnia Severity Index (ISI), and the Pittsburgh Sleep Quality Index (PSQI) for evaluation of benefit. Using the Brainsway dTMS system over the LDPFC at 120% MT for an average of 31 treatments, our study demonstrated benefit for both mood and insomnia. We observed an improvement on the PHQ-9 from 17.3 to 7.53, on the BDI from 30.44 to 11.75, on the ISI from 13.47 to 9.31, and on the PSQI from 11.78 to 9.08. Focusing specifically on the insomnia response, we compared an equal number of both male versus female patients, and those > and < than 65 years of age. Results: Using paired t-test comparisons, men and those less than 65 demonstrated statistically significant improvement. The male population demonstrated statistically significant decreases of t=2.39, 13df, P=.03 on the ISI, and t=2.59, 13df, P=.02 on the PSQI. For women the result was t=1.35, 13df, P=.20 on the ISI, and t=2.05, 13df, P=.06 on the PSQI. In the elderly (>65) decreases were not statistically significant at t=.62, 14df, P=.54 on the ISI, and t=1.26, 14df, P=.23 on the PSQI. For those < 65 years old statistically significant decreases observed were t=3.37, 14df, P=.005 on the ISI, and t=3.5, 14df, P=.004 on the PSQI. Conclusion: TMS treatment of depression resulted in statistically significant benefits on co-existing insomnia in males and those less than 65 years of age. As insomnia may be a precipitating or perpetuating factor in depression and may result in depression relapse, attention to this symptom is of clinical benefit. Support: **No support was given for this study. Dr. Stultz is a speaker for Harmony Biosciences and has served on their advisory committee. She is also a speaker for Jazz Pharmaceuticals. She is the co-editor for the Clinical TMS Society Newsletter and on the education committee.